2007
DOI: 10.1073/pnas.0701946104
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Sp4 regulates dendritic patterning during cerebellar maturation

Abstract: Integration of inputs by a neuron depends on dendritic arborization patterns. In mammals, the genetic programs that regulate dynamic remodeling of dendrites during development and in response to activity are incompletely understood. Here we report that knockdown of the transcription factor Sp4 led to an increased number of highly branched dendrites during maturation of cerebellar granule neurons in dissociated cultures and in cerebellar cortex. Time-course analysis revealed that depletion of Sp4 led to persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 51 publications
5
85
0
Order By: Relevance
“…Among the SP family transcription factors, SP4 is predominantly expressed in neuronal cells (36) and contributes to the transcriptional regulation of neuronal genes, such as neurotrophin-3 (Nt-3) (22). Previous studies also reported that SP4 was involved in neuronal functions such as dendritic patterning in the cerebellum (37), development of the hippocampal dentate gyrus (38), and sensorimotor gating and memory (39). Therefore, the SP4-mediated transcriptional regulation of Arc may be involved in the regulation of several types of physiological functions in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Among the SP family transcription factors, SP4 is predominantly expressed in neuronal cells (36) and contributes to the transcriptional regulation of neuronal genes, such as neurotrophin-3 (Nt-3) (22). Previous studies also reported that SP4 was involved in neuronal functions such as dendritic patterning in the cerebellum (37), development of the hippocampal dentate gyrus (38), and sensorimotor gating and memory (39). Therefore, the SP4-mediated transcriptional regulation of Arc may be involved in the regulation of several types of physiological functions in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…One could theorize that this reduced breakpoint stems from lower NMDAR expression in these mice, but this deficit was not remediated by GlyT-1 inhibition (Figure 4a), unlike that seen for attention (Figure 3). Considering the importance of Sp4 expression during neurodevelopment (Ramos et al, 2007;Zhou et al, 2007), (Figure 5a). This deficit was driven by a reduced likelihood of staying at the target side after being rewarded at that sidehence reduced reward sensitivity (Figure 5c).…”
Section: Discussionmentioning
confidence: 99%
“…The SP4 gene recognizes GC-rich sequences of 'CpG islands' around the promoters of a variety of genes and is neuronally localized (Supp et al, 1996;Zhou et al, 2005). SP4 is therefore highly expressed during neuronal differentiation (Sun et al, 2014;Zhou et al, 2007), and regulates dendritic patterning and neural development during maturation (Ramos et al, 2007;Zhou et al, 2007). Importantly, the SP4 gene was deleted in some patients with schizophrenia (Tam et al, 2010;Zhou et al, 2010), whereas single-nucleotide polymorphisms of SP4 have also been associated with schizophrenia (Zhou et al, 2009), bipolar disorder, and major depressive disorder (Pinacho et al, 2011;Shi et al, 2011;Zhou et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional reconstruction of Z-series images was then performed using a maximum brightness projection algorithm (Volocity imaging software). Images of transfected granule neurons were analyzed using SPOT software for dendritic length and number of primary and secondary dendrites as described previously (Gaudilliere et al, 2004;Shalizi et al, 2006;Ramos et al, 2007).…”
Section: Methodsmentioning
confidence: 99%